Bibliometric Analysis of the Term “Entrepreneurial Motivation” - Mudassir, Andi; Yuswono, Irawan; Usmany, Paul; AJi, Lexi Jalu (IJBLE Scientific Publications Community Inc., 2024)
This study presents a comprehensive bibliometric analysis of the term